Two-degree-of-freedom fractional order-PID controllers design for fractional order processes with dead-time. (March 2016) - Li, Mingjie; Zhou, Ping; Zhao, Zhicheng; Zhang, Jinggang
Abstract: Recently, fractional order (FO) processes with dead-time have attracted more and more attention of many researchers in control field, but FO-PID controllers design techniques available for the FO processes with dead-time suffer from lack of direct systematic approaches. In this paper, a simple design and parameters tuning approach of two-degree-of-freedom (2-DOF) FO-PID controller based on internal model control (IMC) is proposed for FO processes with dead-time, conventional one-degree-of-freedom control exhibited the shortcoming of coupling of robustness and dynamic response performance. 2-DOF control can overcome the above weakness which means it realizes decoupling of robustness and dynamic performance from each other. The adjustable parameter η 2 of FO-PID controller is directly related to the robustness of closed-loop system, and the analytical expression is given between the maximum sensitivity specification M s and parameters η 2 . In addition, according to the dynamic performance requirement of the practical system, the parameters η 1 can also be selected easily. By approximating the dead-time term of the process model with the first-order Padé or Taylor series, the expressions for 2-DOF FO-PID controller parameters are derived for three classes of FO processes with dead-time. Moreover, compared with other methods, the proposed method is simple and easy to implement. Finally, the simulation results are given to illustrate the effectiveness of this method. Highlights: Two degrees of freedom control strategy is extended to fractional order control system. An analytical expression is given between the maximum sensitivity ( M s ) specification and controller parameter about the effect of controller parameters on the system's performance and robustness. Derive the expressions for 2-DOF FO-PID controller parameters by approximating dead-time term with the first-order Padé or Taylor series.